Comparative Study of Religious Understandings of Persatuan Umat Islam (PUI) and Al-Irsyad Al-Islamiyyah (Review of Similarities and Differences in Building Ukhuwah Islamiyah) - Tatang Hidayat; Udin Supriadi (Islam Realitas: Journal of Islamic and Social Studies, 2019)
The phenomenon of the diversity of religious understandings of Islamic mass organizations in Indonesia promotes a variety of attitudes in the midst of society.  The purpose of this study was to analyze the results of a comparative study of religious understanding of Persatuan Umat Islam (PUI) and Al-Irsyad al-Islamiyyah reviewing the similarities and differences in building ukhuwah Islamiyah. This study employed a qualitative approach and a descriptive method.  In relation to the data collection techniques, this study employed several techniques such as interviews, observation, and documentation study. Furthermore, the collected data were analyzed using a descriptive analysis.  Based on the results of the study, it is obvious that the historical background of the establishment of PUI and Al-Irsyad was definitely different with each other. PUI was established as a result of blending the two different Islamic organizations. On the other hand, al-Irsyad was established as the continuation of the former organization called Jamiatul Khair. With respect to the faith understandings, both PUI and al-Irsyad adopted the same understanding, Aqidah ahlus Sunnah wal Jama'ah.  In the realm of worship practices, PUI adopted the understanding of the Shafi'i schools of thought, while Al-Irsyad al-Islamiyyah referred directly to the Qur'an and the Sunnah through the understanding of their scholars. In addition, in understanding Tasawwuf, PUI provided flexibility to each individual in regard to the tarekat involvement, while Al-Irsyad al-Islamiyyah in principle did not adopt the concept of Tasawwuf.  Al-Salam, Ishlah al-Samaniyah, santri asromo, santri lucu and intisab were considered as a series of unique concepts adopted by PUI.  On the other hand, the initial basic principle of the Al-Irsyad Al-Islamiyyah movement was to realize equality in the lives of fellow Muslims based on the understandings as postulated within the Quran and the Sunnah, and to remove the innovation practices (bid'ah) in terms of the faith as stated in the mabadi of Al-Irsyad.  In terms of the charitable efforts, these two organizations put more concern primarily on the realms of religion, education, economy, and social. Therefore, as the implication of this issue, the society will behave wisely in regard to the differences in Islamic understandings of Islamic mass organizations in the midst of society.Fenomena beragamnya paham keagamaan organisasi massa Islam yang ada di Indonesia menimbulkan beragam sikap di tengah-tengah kehidupan masyarakat. Tujuan penelitian ini untuk menganalisis hasil studi komparasi pemahaman keagamaan Persatuan Umat Islam dan Al-Irsyad al-Islamiyyah tinjauan persamaan dan perbedaan dalam membangun ukhuwah Islamiyah. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif. Teknik pengambilan data dengan wawancara, observasi dan studi dokumentasi.  Data-data yang sudah diperoleh kemudian dianalisis melalui analisis deskriptif. Berdasarkan hasil penelitian, terdapat perbedaan sejarah berdirinya PUI dan Al-Irsyad. PUI terlahir dari gabungan 2 ormas Islam yang berbeda, adapun Al-Irsyad terlahir dari ormas Jamiatul Khair. Dalam pemahaman ‘aqidah, PUI dan Al-Irsyad sama-sama menganut paham ‘aqidah Ahlus Sunnah wal Jama’ah. Dalam pengamalan ibadah, PUI mengadopsi pemahaman madzhab Syafi’i rahimahullah, adapun Al-Irsyad al-Islamiyyah merujuk langsung kepada al-Qur’an dan Sunnah melalui pemahaman ulama mereka. Dalam pemahaman Tasawuf, PUI memberikan keleluasaan kepada pribadi masing-masing untuk mengikuti tarekat manapun, adapun Al-Irsyad al-Islamiyyah secara pemahaman tidak mengadopsi konsep tasawuf. PUI memiliki prinsip khas yakni konsep al-Salam, Ishlah al-Samaniyah, santri asromo, santri lucu dan intisab. Adapun prinsip pokok awal gerakan Al-Irsyad al-Islamiyyah yakni mewujudkan kesetaraan dalam kehidupan sesama muslim berdasar pemahaman yang bersumber dari al-Quran dan sunnah, menumpas praktik bid’ah dalam hal akidah sebagaimana yang tercantum dalam mabadi Al-Irsyad al-Islamiyyah.  Dari segi amal usaha kedua ormas ini memiliki kesamaan dalam bidang keagamaan, pendidikan, ekonomi, dan sosial. Implikasinya dalam menyikapi perbedaan paham keagamaan ormas Islam di tengah-tengah masyarakat akan semakin bijaksana.